Le reti alternative del cibo dopo la crisi. Teoria, ipotesi di lavoro e un caso studio esplorativo - Giovanni Orlando (Archivio Antropologico Mediterraneo)
This article asks how Italian alternative food networks have changed after the global economic crisis of 2008. The article analyzes the phenomenon in question through the use of two bodies of literature, the anthropology of value (deployed in the direction of food studies) and food regimes theory. After discussing the literature in reference to the central question, the article develops four hypotheses to try to answer it. These are: 1) generation, 2) strengthening, 3) obstruction and 4) irrelevance. In the second half of the article, a specific example of alternative food network called Fuori Mercato (‘outside the market’) is examined as a possible illustration of the first hypothesis, that of generation.